2011
DOI: 10.1016/j.exer.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the aqueous humor outflow pathway in human eyes by three-dimensional micro-computed tomography (3D micro-CT)

Abstract: The site of outflow resistance leading to elevated intraocular pressure in primary open angle glaucoma is believed to be located in the region of Schlemm's canal inner wall endothelium, its basement membrane and the adjacent juxtacanalicular tissue. Evidence also suggests collector channels and intrascleral vessels may have a role in intraocular pressure in both normal and glaucoma eyes. Traditional imaging modalities limit the ability to view both proximal and distal portions of the trabecular outflow pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
1
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 48 publications
4
92
1
15
Order By: Relevance
“…Ascher 11 reported that 2 aqueous veins are sufficient to drain the aqueous produced daily. Hann et al 12 have proposed that the aqueous outflow pathway is composed of individual functional regions. This is analogous in concept to areas drained by renal papillae in the kidneys, 12 where preferential and segmental flow patterns have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascher 11 reported that 2 aqueous veins are sufficient to drain the aqueous produced daily. Hann et al 12 have proposed that the aqueous outflow pathway is composed of individual functional regions. This is analogous in concept to areas drained by renal papillae in the kidneys, 12 where preferential and segmental flow patterns have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Hann et al 12 have proposed that the aqueous outflow pathway is composed of individual functional regions. This is analogous in concept to areas drained by renal papillae in the kidneys, 12 where preferential and segmental flow patterns have been described. 13,14 Recently, it was reported that the SC showed segmental heterogeneities of the lymphatic-specific transcriptional factor prsopero homeobox protein 1 (PROX1) expression, which masters the regulator of lymphatic development.…”
Section: Discussionmentioning
confidence: 99%
“…Hann et al [31] veröffentlichten 2011 eine 3-dimensionale Darstellung der Kammerwasser ableitenden Strukturen, die mittels 3D-Micro-CT an 2 humanen Augen in vitro gewonnen wurden (. Abb.…”
Section: Abflusswege Jenseits Des Schlemm-kanalsunclassified
“…Trabekelmaschenwerkszellen reagieren dynamisch auf mechanische Eigenschaften wie die Rigidität ihrer Umgebung oder Flüssigkeitsströmungen [2][3][4]. Bei der Pathogenese des primären Offenwinkelglaukoms spielen sowohl extra-wie auch intrazelluläre Umbauvorgänge eine Rolle, die zusammengenommen eine Erhöhung des Abflusswiderstands nach sich ziehen [5,6] [7,8]. Für einen Überblick über die Anatomie und Physiologie der Abflusswege sowie ihre Beteiligung bei der Glaukomentstehung sei auf einen kürzlich von Tamm veröffentlichten Übersichtsartikel verwiesen [9].…”
unclassified